A review of analytical and optimization methodologies for transitions in multi-scale energy systems. (May 2022) - Kakodkar, R.; He, G.; Demirhan, C.D.; Arbabzadeh, M.; Baratsas, S.G.; Avraamidou, S.; Mallapragada, D.; Miller, I.; Allen, R.C.; Gençer, E.; Pistikopoulos, E.N.
Abstract: Reliable access to clean and affordable energy is a prerequisite to socio-economic progress. Meeting the global energy demand in the face of a burgeoning population and increases in per capita consumption of energy mandates a cost-conscious transition towards efficient and sustainable technologies. Key challenges towards the realization of renewable energy systems include pronounced spatio-temporal variability in renewable resource availability, geographic limitations for resources and technologies, increase in energy and material demands, and the need to drastically reduce emission while remaining sensitive to costs. Some opportunities such as sector coupling, the use of chemical energy carriers and alternative energy feedstocks, carbon capture and sequestration, policy and taxation initiatives, and increased electrification can address these challenges if implemented in a systematic and coordinated manner by well informed decision makers. To this end, we propose the elements necessary for quantitative system-level analysis at different temporal and geographic resolutions, and present decision-making tools that can account for spatial as well as temporal variability of available resources, technologies, production targets, demands, and policy choices. We provide four motivating examples to demonstrate the use of these tools in determining sustainable transition pathways. These include the direct and indirect electrification of transportation, the production of chemical energy carriers, hydrogen infrastructure, and policies to encourage and accelerate the transition. Highlights: A review of computational tools and methods to accelerate the energy transition. Addressing demand and supply side variabilities and intermittencies, and geographic limitations. Role of sector integration, alternative energy sources and carriers, carbon capture, and policy.